Major Variation in Branches of the Abdominal Aorta in New Zealand White Rabbit (Orycotolagus Cuniculus) - Ahasan, ASML; Islam, MS; Kabria, ASMG; Rahman, ML; Hassan, MM; Uddin, M (International Journal of Natural Sciences, 2013)
The aim of the present study was to investigate the arrangement and major vascular variation of abdominal aorta in NZW rabbit. A total of 28 healthy adult rabbits (14 males and 14 females) with an average (1.3 ± 0.5kg) body weight were used in this study. Deep surgical anaesthesia was done by using combination of xylazine and ketamine at the doses of 10mg/kg and 40mg/kg body weight respectively, and was sacrificed by bleeding through the right ventricle of the heart. Cannulation of the thoracic aorta and stained latex (added with ammonium water and red carmine stain) injection were performed, followed by 10% neutral buffered formalin. Asymmetry of the even branches with their distribution and the way of departure of the arteries from the abdominal aorta were observed. However, double pair ovarian arteries were found in a single animal. The diameter of the caudal mesenteric artery showed significant (p?0.05) difference between male and female. In case of male and female, the variability of the origin (number and level of origin) of testicular, ovarian and profound iliac circumflex arteries was also observed. DOI: http://dx.doi.org/10.3329/ijns.v2i4.13218 International Journal of Natural Sciences (2012), 2(4) 91-98